AB1215 Minimal invasive ultrasound-guided parotid gland biopsy in cadavers done by rheumatologists. (12th June 2018) - Micheroli, R.; Wagner, U.; Mueller-Gerbl, M.; Toranelli, M.; Marx, C.; Bruyn, G.A.W.; Jousse-Joulin, S.; Tamborrini, G.
Abstract : Background: In daily practice, surgical biopsy of minor salivary glands is routinely performed for the diagnosis of Sjögren's syndrome. The classification criteria for Sjögren's syndrome imply specific positive labial salivary gland biopsy findings. Surgical biopsies of the minor labial glands may result in up to 6% of patients in various complications, e.g. numbness of the lower lip. On the other hand, adverse events following core needle biopsies of the parotid gland in non-rheumatological settings were reported as very rare. Even so parotid gland biopsies require a more demanding surgical expertise mainly to protect the facial nerve. Objectives: The objective of this study was to assess the feasibility and to determine the presence of parotid gland tissue in minimally invasive ultrasound-guided parotid gland biopsies in cadavers performed by rheumatologists using histology as a gold standard. Methods: Two senior rheumatologists obtained under direct ultrasound visualisation in in-plane technique biopsies of 8 parotid glands from 4 different cadavers using a core biopsy needle (core biopsy needle 18G). One biopsy per gland was taken and was subsequently stored. The direction of the bioptic access is shown in Figure 1. The specimen underwent histological examination by an experienced pathologist. Results: All histological exams showed typical parotid gland tissue. Notably, no facial nerve tissue or major vessels could be detected in the biopsy material. Conclusions: In this cadaveric feasibility study, we demonstrated that minimally invasive ultrasound guided parotid core biopsy is a highly precise and easy method to obtain salivary gland tissue. References: [1] Shiboski C. H. et al, 2016American College of Rheumatology/European League Against Rheumatism Classification Criteria for Primary Sjogren's Syndrome. Arthritis Rheumatol. 2017 Jan;69(1):35–45. [2] Kim H.Jet al, Ultrasound-Guided Core Needle Biopsy in Salivary Glands: A Meta-analysis, Laryngoscope, 00:000–000, 2017. Disclosure of Interest: None declared